Car Parking Needs Analysis at Campus a Jakarta State University In The Construction Period - Puspa Wangi, Intan; Lenggogeni, Lenggogeni; Hadi, Winoto (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Parking is the main supporting facility in the campus environment. Jakarta State University (UNJ) is one of the state universities in the DKI Jakarta province. The increase in the number of UNJ students every year certainly causes an increase in the need for parking, especially on Campus A UNJ as the main campus. Coupled with a construction project in Campus A UNJ, the parking area, especially car parking, is getting narrower. Based on these problems, it is necessary to research parking arrangements at Campus A UNJ. This study aims to determine the need for parking and arrange the car parking area for Campus A UNJ according to the demand for car parking space that existed during the construction period. The parking space arrangement for Campus A UNJ considers UNJ's policy as the manager in allocating parking spaces in the future. Primary data was obtained by conducting a field survey using the number plate survey method and PSU calculation survey while secondary data was obtained from UNJ parking inventory data. Primary data were obtained by conducting field surveys on 29 May-31 May and 8-9 June. The results showed that the value of the need for car parking in 2023 was 367 PSU cars, while the number of parking lots available at Campus A UNJ was 389 PSU. The peak day occurs on Tuesday 30 May 2023 and the peak hour for parking accumulation occurs at 13.00-14.00 WIB. With a parking index close to 100%, this can make it difficult for drivers to find an empty parking space, especially considering the pattern of car parking in the UNJ campus A parking area rotates in one direction so that the opportunity to find an empty parking space during peak parking hours only has a one-time or one-time chance. parking spaces at peak parking hours only have a one-time chance or the driver must first exit the parking lot and then enter again to find an empty parking space. The arrangement of car parking modeling will also be presented in this article. It is hoped that the results of this early-stage research can provide an overview and recommendations on parking management methods at Campus A UNJ.